VIOLATIONS OF HUMAN RIGHTS AND PROTECTION BY UNICEF ON THE USE OF CHILD SOLDIERS IN CONGO'S ARMED CONFLICT - Putu Marta (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2023)
This article aims to find out the human rights violations that occurred in child soldiers in the armed conflict of the Congo. Human rights are basic rights that are owned by every human being as a gift from God Almighty, valid for life, and cannot be contested. Recruiting children as soldiers is a violation of human rights. Protection of children's rights is an inseparable part of human rights. emotionally, physically, and psychologically on children are the negative impacts of the presence of child impact soldiers. Unstable government conditions coupled with a low economy add to the burden on society which pushes their children to fall into the circle of militarization. The real form of protection for children who are recruited into child soldiers is the protection provided by UNICEF. UNICEF pays great attention to children's settlement.